Pengaruh Pemberian Kompos Isi Rumen Sapi terhadap Pertumbuhan Bibit Kelapa Sawit (Elaies guineensis Jacq.) di Main Nursery - Gita, Isna; Suliansyah, Irfan; Noferta, Ade (Jurusan Budidaya Pertanian Fakultas Pertanian Universitas Andalas, 2022)
The purpose of this study was to see and determine the effect of application of cow rumen compost on the growth of oil palm seedlings (Elaies gueneensis Jacq.) in main nursery. This research was carried out in the experimental garden of the Agroecotechnology Department, Faculty of Agriculture, Andalas University from September 2018 to February 2019. This research was conducted whit 5 treatments and 5 replications, each of which consisted of 2 units of plant experiments. Doses of compost were 0 g, 250 g, 500 g, 750 g and 1000 g. The parameters observed were plant height, leaf length, leaf width, number of leaves, and stem diameter. The data obtained were analyzed by variance with a level of 5% if significantly different followed by Duncan’s New Multiple Range Test (DNMRT) at 5% level. The application of 1000 g compost gave the best result on plant height, leaf length, leaf width, leaf number, and hump diameter.